Isolated and stable gallbladder perforation in a 5 year old child after blunt abdominal trauma. (June 2017) - Issa, I.; Modica Alameddine, V.; Fadous Khalife, M.C.; Al Ojaimi, M.; Ghorayeb, Z.
Abstract: Isolated gallbladder injury, secondary to a blunt abdominal trauma, is a rare finding in children. The presence of vague symptoms and the unknown dynamic of the trauma may increase the diagnostic challenge especially in pediatrics. A conservative management has been proposed in some particular cases in adults, but remains controversial in children. We report a case of a 5 year old boy who presented an isolated gallbladder lesion secondary to a blunt abdominal trauma. The surgical treatment was delayed for non-medical reasons, which gave us the possibility to try a conservative approach.